Implementing the Stability and Growth Pact : Enforcement and Procedural Flexibility - Beetsma, Roel (IMF Working Papers; Working Paper ;, 2005)
The paper analyzes some key policy trade-offs involved in the implementation of the Stability and Growth Pact. Greater "procedural" flexibility in the Pact's implementation may improve welfare. Procedural flexibility designates the enforcer's room to apply judgment on underlying policies and to set a consolidation path that does not discourage high-quality measures. Budgetary opaqueness may hinder the qualitative assessment of fiscal policy; therefore, better monitoring and greater transparency would increase the benefits from procedural flexibility. Overall, a simple deficit rule with conditional procedural flexibility can contain excessive deficits, lower unproductive spending, and increase high-quality outlays.